Mengintegrasikan budaya dalam pembelajaran matematika kontekstual: strategi peningkatan kemampuan numerasi siswa sekolah dasar - Afifah, Putri Nur; Faizah, Hanim (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study addresses deficient numeracy literacy among elementary students by implementing a local culture-based Contextual Teaching and Learning (CTL) model, utilizing the traditional "dakon" game to teach Least Common Multiple concepts. Design/methodology/approach: This quantitative study employed a pre-experimental design involving fifth-grade elementary students. Data were collected through descriptive tests aligned with numeracy indicators, validated by subject matter experts and educational practitioners.Findings: Statistical analysis revealed a significant improvement in students' numeracy skills. The integration of the dakon game effectively bridged the gap between abstract and concrete concepts, while substantially increasing student engagement, discussion participation, and enthusiasm in problem-solving.Practical implications: This study serves as a reference for educators to transform mathematics instruction into an interactive experience by leveraging indigenous wisdom as a relevant instructional medium for students.Originality/value: The novelty of this study lies in the systematic integration of the seven-stage CTL framework with ethnomathematics elements through traditional gameplay to strengthen numerical literacy in primary education.   Purpose: Penelitian ini bertujuan mengatasi rendahnya literasi numerasi siswa sekolah dasar melalui implementasi model Contextual Teaching and Learning (CTL) berbasis budaya lokal dengan media permainan tradisional dakon pada materi Kelipatan Persekutuan Kecil (KPK). Design/methodology/approach: Penelitian kuantitatif ini menggunakan desain pre-eksperimen terhadap siswa kelas lima sekolah dasar. Data dikumpulkan melalui tes uraian yang disusun berdasarkan indikator numerasi dan telah divalidasi oleh ahli materi serta praktisi pendidikan. Findings: Hasil uji statistik menunjukkan perbedaan signifikan antara kemampuan awal dan akhir siswa. Integrasi permainan dakon terbukti efektif menjembatani konsep abstrak menjadi konkret, serta secara nyata meningkatkan keterlibatan aktif, keberanian berdiskusi, dan antusiasme siswa dalam memecahkan masalah matematika. Practical implications: Studi ini menjadi acuan bagi pendidik untuk mentransformasi pembelajaran matematika menjadi lebih interaktif dengan memanfaatkan kearifan lokal sebagai media instruksional yang relevan dengan keseharian siswa. Originality/value: Kebaruan studi ini terletak pada penggabungan struktur tujuh tahap CTL secara sistematis dengan unsur etnomatematika melalui permainan tradisional untuk memperkuat literasi numerik pada jenjang pendidikan dasar.